Study on capacity planning in a woven garment industry to increase productivity - Yasmin Sabina; Jannatul Noor; Solaiman Md; Mahamudul Hasan Mojumder; Hossain Delwar; Chowdhury Joyjit; Shahjalal Md (Tekstilna industrija)
In today's fast-paced world, fashion and styles are constantly evolving. The rapid changes in fashion have led to the need for shorter production cycles in the garment industry. Running a garment manufacturing operation today requires a scientific and professional approach. Industrial engineering principles are essential at every stage, including costing, product research and development, planning, supply chain management, product management, layout design, productivity enhancement, and workforce skill development. The objective of this project is to accurately motivate and train the operators by increasing their skill to achieve the highest capacity and productivity of the industry. And make ensure the delivery into committed date. For this experiment we choose a 5 pocket jeans pant. Capacity study is the most important tool for increase productivity. This study helps to identify bottleneck and suggest the way to reduce the bottleneck to improve the productivity. We use the cycle time, SAM to determine the capacity of the woven garment industry. After we determine the both capacity of before and after IE work of the factory; then we can see that the hourly capacity increased 13 pcs. & daily capacity increased 126 Pcs.